2010
DOI: 10.12741/ebrasilis.v2i3.59
|View full text |Cite
|
Sign up to set email alerts
|

Arreglo de los polígonos del exocorion de huevos eclosionados de algunas especies de los géneros Triatoma Laporte, Meccus Stal y Nesotriatoma Usinger (Heteroptera: Reduviidae).

Abstract: Resumen. En este trabajo se estudiaron estructural y cuantitativamente las celdas exocoriales de huevos eclosionados de Triatoma infestans (Klug), Triatoma lenti Sherlock & Serafim, Triatoma maculata (Erichson), Triatoma sordida (Stal), Meccus picturatus (Usinger), Meccus longipennis (Usinger), Meccus pallidipennis (Stal) y Nesotriatoma flavida (Neiva). Los huevos se analizaron por regiones: caudal, media y cefálica. Se encontró que el hexágono fue el polígono más abundante en todas las regiones del huevo y en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The taxonomic value of morphological characteristics related to the exochorial structure of eggs for the differentiation of triatomines, as observed in the present study, has been demonstrated since the 1930s, based on the study of the egg exochorium from specimens of the genera Rhodnius and Triatoma ( Galliard 1935 ). Similarly, morphological (using OM or SEM) and morphometric approaches have been conducted for the characterization and taxonomic differentiation of other species of the genus Triatoma that occur in the Cerrado Biome, including T. brasiliensis ( Costa et al 1997 ), Triatoma sordida (Stål, 1859) ( González et al 2009 ), T. pseudomaculata ( Gonçalves et al 1985 ), T. williami ( Silva et al 2005 , Obara et al 2007 ), and T. costalimai ( Obara et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic value of morphological characteristics related to the exochorial structure of eggs for the differentiation of triatomines, as observed in the present study, has been demonstrated since the 1930s, based on the study of the egg exochorium from specimens of the genera Rhodnius and Triatoma ( Galliard 1935 ). Similarly, morphological (using OM or SEM) and morphometric approaches have been conducted for the characterization and taxonomic differentiation of other species of the genus Triatoma that occur in the Cerrado Biome, including T. brasiliensis ( Costa et al 1997 ), Triatoma sordida (Stål, 1859) ( González et al 2009 ), T. pseudomaculata ( Gonçalves et al 1985 ), T. williami ( Silva et al 2005 , Obara et al 2007 ), and T. costalimai ( Obara et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a specific example, one of us (E.A.) showed that in Chagas disease vector (insects from the Triatominae subfamily), egg morphology design and variability are strongly controlled by architectural rules and mechanisms of nutrient interchange (Aldana, Arriechi, & Lizano, 2013;Aldana, Avendaño-Rangel, Lizano, Rodríguez-Bonfante, & Bonfante-Cabarcas, 2011;González, Aldana, Lizano, & López, 2009;Páez-Colasante & Aldana, 2008;Sandoval, Nieves, Angulo, Rosa, & Aldana, 2011). Hence, orthogenetic and constructional morphology principles may be the main mechanisms involved in egg design.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, given that the phenotypical expression is not limited only by restrictions on their functioning but also by the way they were made (physical restraints) and by their past (historical and phylogenetic limits), it must be supposed that the driven force could be as much historicalgenetic as environmental (sensu De Renzi 2009;Dusenbery 2001; Figure 1). The theory of functional morphology or biomorphodynamics has advanced considerably towards this neo-evolutionary line of thinking (De Renzi 2009) and has allowed us to understand better the triatomines' evolution (e.g., González et al 2009). This review will offer a sketch of the phylogeny and radiation of the group and will show how these insects could have overcome, and even taken advantage of, several physical and ancestral barriers to adapt to bloodsucking of a nidicolous host.…”
Section: Introductionmentioning
confidence: 99%